Unlocking the ideal home: exploring user preferences and sustainable green residential house features for smart buyers/ Muhammad Naseh Mohamad Tarmizi ... [et al.] - Mohamad Tarmizi, Muhammad Naseh; Mohd Noor, Siti Nur Aishah; Ramly, Mohd Khairul Amri; Naamandadin, Nurul Akmam (Universiti Teknologi MARA, Perak, 2023)
With an increasing emphasis on environmentally friendly lifestyles, buyers are increasingly attracted to green factors when purchasing a house. However, many residential houses fail to meet the characteristics of green buildings, resulting in environmental pollution. This research aims to identify buyer preferences when buying a house and determine the desired characteristics of green residential buildings. Factors such as price, location, neighbourhood, structural design, and lifestyle considerations influence buyers' decisions. Additionally, the research examines specific features of green residential buildings, including green building certification, sustainable materials, waste management and recycling, native landscaping, and passive design strategies. In this paper, the research methodology uses quantitative data. The findings revealed that a significant number of buyers prioritise green features for residential properties when making a house purchase. This sheds light on the factors that influence consumer choices and emphasises the need for sustainable housing options in the real estate market. This research offers valuable insight for policymakers, developers, and industry professionals seeking to align housing offerings with the growing demand for green and sustainable living.